Chemical processing of interfacially assembled metal nanowires for surface‐enhanced Raman scattering detection of food contaminants. (24th November 2020) - Duan, Bo; Hou, Shuai; Wang, Peng; Chen, Yonghao; Xiong, Qirong; Das, Paramita; Duan, Hongwei
Abstract: We report a new strategy for the fabrication of Ag–Au bimetallic nanowire (NW) arrays by taking advantage of interfacial assembly of plasmonic nanoparticles and galvanic replacement reactions. Galvanic replacement reactions led to the formation of nanospikes on NWs, giving rise to a high density of hotspots across the entire NW array. We employed this NW array as a surface‐enhanced Raman scattering (surface‐enhanced Raman spectroscopy [SERS]) substrate for the detection of two types of food contaminants: thiram (a pesticide) and melamine (an adulterant). Limits of detection (LODs) of 1 and 10 nM were achieved for thiram in juice samples and melamine in milk samples, respectively. Both LODs are lower than the maximum acceptable concentrations imposed by the US government. The results demonstrate tremendous practical potential of Ag–Au NW arrays as surface‐enhanced Raman scattering substrates for the detection of food contaminants. Abstract : Ag–Au nanowire arrays were employed as two‐dimensional SERS substrates for the detection of food contaminants. The substrate was fabricated by interfacial self‐assembly of Ag nanowires and subsequent galvanic replacement reactions. Nanospikes formed on the nanowire surfaces led to the generation of a high density of hotspots across the entire nanowire arrays.